2018
DOI: 10.1590/1981-52712015v42n2rb20170070
|View full text |Cite
|
Sign up to set email alerts
|

Enfrentamentos do Estudante na Iniciação da Semiologia Médica

Abstract: RESUMO Introdução: Uma das maiores expectativas do acadêmico de KEYWORDS-Anamnesis.-Physical Examination.-Medical Education.-Medical Psychology. ABSTRACT Introduction

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
2
0
8

Year Published

2019
2019
2022
2022

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 12 publications
(11 citation statements)
references
References 17 publications
1
2
0
8
Order By: Relevance
“…Our study showed that UNESC medical students' mean age is 23 years, with a predominance of females and Caucasians, which meets the demographic profile shown in other studies carried out with medical students in Santa Catarina 8 , and also in other states such as Goiás 13 , Paraíba 14 ones that most often considered the PT an important way to guarantee knowledge through memorization, and consequently appropriation of knowledge 13 . There was also a demand by these students that there should be discussions with the teachers about the test and feedback, after they had taken it.…”
Section: Discussionsupporting
confidence: 85%
“…Our study showed that UNESC medical students' mean age is 23 years, with a predominance of females and Caucasians, which meets the demographic profile shown in other studies carried out with medical students in Santa Catarina 8 , and also in other states such as Goiás 13 , Paraíba 14 ones that most often considered the PT an important way to guarantee knowledge through memorization, and consequently appropriation of knowledge 13 . There was also a demand by these students that there should be discussions with the teachers about the test and feedback, after they had taken it.…”
Section: Discussionsupporting
confidence: 85%
“…Nosso estudo demonstrou que os acadêmicos do curso de Medicina da UNESC têm uma média de idade de 23 anos, com predominância do gênero feminino e caucasianos, o que vai ao encontro do perfil demográfico verificado em outros estudos realizados com estudantes de Medicina em Santa Catarina 8 e também em outros estados, como Goiás 13 , Paraíba 14 e Rio Grande do Norte 15 .…”
Section: Discussionunclassified
“…Sendo assim, após a análise e com base nos temas identificados, os artigos foram classificados nas seguintes categorias: a arte mobilizando o ensino; o processo de avaliação; a formação e as percepções de docentes; o uso de tecnologias digitais no ensino médico; as percepções de alunos sobre o ensino médico; metodologias ativas de ensino-aprendizagem; relatos de experiência de instituições de ensino médico sobre a reformulação curricular; relatos de experiência sobre a reformulação de disciplinas; e o repensar sobre a educação médica. (OLIVEIRA et al, 2018), e disciplinas integradoras (CAVALCANTE et al, 2018b;DE SOUZA et al, 2018).…”
Section: Abstração E Síntese Dos Dadosunclassified